A New Political Pacifism: Churches in the Wake of the Great War - Marty, William R. (Journal of interdisciplinary studies, 2018)
In the aftermath of the carnage of World War I, a politically engaged pacifism spread rapidly among a number of traditionally non-peace churches, and among the populations of England and America. This pacifism meant to be effective in the world, and it was: it swayed the democracies of England and America to adopt many of its policies. It meant to achieve peace and end war. Represented as what Christian love requires in political life, it failed utterly and completely in its aims both as political prescription and understanding of Christianity. The relevance of this essay is that many of the erroneous assumptions and failed policies of the church peace movement of the 1930s appear to be still the assumptions and policies of secular statesmen of the present. The errors of the political pacifists live on, and if they are not corrected, the consequences are likely to be the same, or worse, for next time, unless we are wiser than the last, the evil ones may prevail.